A Study of Internal Factors Determining Organizational Choice of Entry Mode to Foreign Markets - Yerseitova, Dana (2010)
This research investigates organizational internal factors determining the choice of entry mode to foreign markets. The internal factors investigated in this research were based on the precedent studies in a chosen field. The factors examined for the purpose of this research included organizational international experience, organizational degree of control, management’s attitude towards risks and diversity in the organization. The study defines each of the factors and explains the relationship between those factors and the dependent variable of this study – choice of entry mode to the foreign market. The study revealed the items constructing variables to belong to various factors. Therefore, the research showed unpredictable results and the direction was changed in comparison to this proposed originally by the researcher. Nevertheless, the study achieved its aim of identification of factors influencing the choice of entry mode and methods of avoiding challenges in foreign market. In addition to that, this study with the aim of the factors analysis determined the factors that influence the organization’s ability to create advantage of product line in foreign market. In addition to that the research provides guideline for the further studies to be conducted in the field of strategic management and, especially, on the challenges associated with the company’s entrance to foreign market in order to fill gaps in this broad field of study.